A Facile Strategy to Support Palladium Nanoparticles on Carbon Nanotubes, Employing Polyvinylpyrrolidone as a Surface Modifier (Eur. J. Inorg. Chem. 9/2014). Issue 9 (March 2014) - Cardoso, Mariana B. T.; Lewis, Edward; Castro, Pollyana S.; Dantas, Luiza M. F.; De Oliveira, Caio C. S.; Bertotti, Mauro; Haigh, Sarah J.; Camargo, Pedro H. C.
Abstract : The cover picture shows the deposition of palladium nanoparticles (Pd NPs) on the surface of carbon nanotubes (CNTs) by a simple strategy employing ethanol as the solvent/reducing agent, potassium tetrachloropalladate(II) (K2 PdCl4 ) as the Pd precursor, and polyvinylpyrrolidone (PVP) as the surface modifier. More specifically, the approach is based on the nonbonding interaction between PVP and the CNTs and does not require any additional functionalization steps, reducing agents, or stabilizers to uniformly distribute Pd NPs on the CNTs. Details are discussed in the article by S. J. Haigh, P. H. C. Camargo et al. onp. 1439 ff . For more on the story behind the cover research, see theCover Profile .